Excess Weight Gain in Pregnant Women and Prematurity: A Meta-Analysis - Damalita, Annisa Fitriana; Dewi, Yulia Lanti Retno; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2022)
Background: Premature birth as a cause of morbidity and mortality in neonates. Excessive weight gain in pregnant women is considered a risk factor for adverse pregnancy outcomes including preterm birth. This study aims to analyze the effect of excess weight gain in pregnant women on premature birth. Subjects and Method: This research is a systematic review and meta-analysis. Article searches were conducted using electronic databases such as Google Scholar, PubMed, Science Direct and Springerlink. The articles used are articles published from 2011-2021. The keywords to search for articles were: “gestational weight gain” AND “pregnancy” AND (“preterm birth” OR “premature birth”) AND “cohort study” AND “adjusted odds ratio”. The inclusion criteria used were full text articles in English with a cohort study design, multivariate analysis with Adjusted Odds Ratios (aOR), research subjects were pregnant women, intervention was excessive weight gain, comparison was normal weight gain (adequate). , the study outcome was preterm delivery (<37 weeks). The article search results are listed in the PRISMA diagram and analyzed using the Review Manager 5.3 application. Results: A total of 10 cohort study articles from China, Indonesia, Canada, Korea, Mexico, Puerto Rico, Saudi Arabia, and Taiwan were selected for systematic review and meta-analysis. The results showed that excess weight gain in pregnant women increased the risk of preterm birth and was statistically significant (aOR= 1.23; 95% CI= 1.01 to 1.48; p= 0.030). Conclusion: Excess weight gain in pregnant women increases the risk of premature birth.